Atuação e formação em estimulação precoce : caracterização da percepção dos profissionais em três instituições - Bobrek, Andreia (Universidade Federal de São Carlos, 2014)
In Brazilian context, the official guideline recommends that Early Stimulation have the purpose of providing the development of children with special needs. In the use of the institutions, this practice involves different types of professionals and of guided acquirements to children with risk to their development. The diversity of practices makes it relevant to describe the performance of the professionals that work in Early Stimulation programs as a way of enabling the improvement of the work carried out, aiming the harmonization of concepts, guidelines and practices. In this research, the purpose was to describe the performance of 13 professionals experienced in working at early stimulation programs, in three institutions, and to analyze the relationships established by these professionals between their professional practice and the knowledge acquired during graduation course. For this purpose, an exploratory study was carried out, whose data collection consisted of semistructured interviews with the abovementioned professionals and the collection of the institutions’ data through consults to the coordination and to the available documents. Regarding the results, the interviewed professionals conceived early stimulation as the provision of opportunities to the child’s development; and/or support to the Family or the prevention of risk for the development. The professionals considered it important for a good service in the early stimulation program the professional involvement and/or specific working conditions and/or partnership with the family. Regarding the difficulties faced in carrying out the work, the reports were focused on the lack of familiar participation/involvement, the inadequacy of work conditions and the work with the child itself. Regarding the preparation/training that the Higher Education Institution (HEI) offered for the work in early stimulation program, eight interviewed professionals informed that the graduation course offered the training on the Early Stimulation; however, half of them related that this training was inadequate/superficial. From the thirteen professionals, five declared that the HEI did not offer preparation/training to work with early stimulation. From all the professionals, tem considered that the HEI could have offered better training, even those that offered some; from those tem, five declared that there should be better articulation between theory and practice.
Acting and practice in Early Stimulation: characterization of the perception of professionals in three institutions
Keywords: Educação especial; Estimulação precoce; Atuação profissional; Formação profissional; Special Education; Early Intervention; Professional practice; Professional training; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO